THE EFFECT OF LIGHT ON GROWTH OF CASSAVA AND SORGHUM I LIGHT DISTRIBUTION AND EXTINCTION COEFFICIENT - Tania June (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1993)
Abstract is available in the full text (pdf format)